Perencanaan tanggul bronjong sebagai preventif kecelakaan kerja mobilisasi angkut sawit - Kartika Setiawati; M Adip Uli Nuha (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Infrastructure development at PT Gunung Sejahtera Puti Pesona (GSPP), especially roads, has raised the potential for serious workplace accidents. To address this issue, a gabion retaining wall is planned as a preventive solution. The gabion project, designed as soil retention and a road safety barrier, aims to address core issues related to unsafe road conditions and slope landslides. This research provides a significant practical contribution to occupational safety in oil palm plantations, particularly in developing accident risk mitigation methods. Through comprehensive analysis of risk factors and the application of a more effective mitigation approach, this research aims to (1) create a gabion retaining wall model as a road safety barrier in the PT GSPP plantation using BIM software; (2) assess the road safety factors from the gabion model; and (3) determine the cost of work needed through a cost budget calculation. This study employs a quantitative method since the data to be processed consists of ratio data, with a primary focus on assessing the influence between the variables studied. The research produces a gabion design with dimensions of 2x1x1 meters, planned for installation along a 45-meter stretch of road with a slope height of 4 meters. The gabion modeling uses Revit 2023, based on Indonesian National Standards (SNI) 03-0090-1999 and the safety factor calculation (SNI) 03-2446-1991. The project’s Cost Budget Plan (RAB) indicates a total cost of IDR 615,444,891.00. This plan considers SNI standards to ensure road safety and minimize workplace accident risks. Implementing the gabion wall is expected to reduce the risk of dump trucks falling off slopes, thereby enhancing worker safety and ensuring smooth operations.